2020
DOI: 10.11604/pamj.2020.37.50.24307
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of COVID-19 prevention among community health workers in rural Cross River State, Nigeria: implications for disease control in Africa

Abstract: Introduction in developing countries, community health workers (CHWs) are essential, for provision of behaviour change communication towards prevention of coronavirus 2019 (COVID-19) infection at rural grassroots level. We aimed at assessing their level of knowledge and practice of preventive measures in a developing country setting. Methods total enumeration of all CHWs in a rural local government area in southern Nigeria was carried out, using cross-sectional descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
2
13
2
5
Order By: Relevance
“…Furthermore, the proper wearing of the mask was not ascertained in those online series. Yet, the figure in the present series is higher than what was recorded amongst heads of households in Enugu metropolis (33.8%) and among CHWs in Cross Rivers State (50%) which was attributed among others, to inadequate provision of the necessary materials [8,22]. Nevertheless, it is worrisome that only 28.5% of participants wore their masks properly, covering both the nose and mouth.…”
Section: Consideringcontrasting
confidence: 70%
See 2 more Smart Citations
“…Furthermore, the proper wearing of the mask was not ascertained in those online series. Yet, the figure in the present series is higher than what was recorded amongst heads of households in Enugu metropolis (33.8%) and among CHWs in Cross Rivers State (50%) which was attributed among others, to inadequate provision of the necessary materials [8,22]. Nevertheless, it is worrisome that only 28.5% of participants wore their masks properly, covering both the nose and mouth.…”
Section: Consideringcontrasting
confidence: 70%
“…The steps of hand washing were however, not explored in this series. On the other hand, hand hygiene practice was reported to be poor (56.4%) in the Cross Rivers state study, which is worrisome as failure to effectively practice preventive measures among CHWs may expose them to the risk of getting infected and spreading the virus in their community [22].…”
Section: Consideringmentioning
confidence: 98%
See 1 more Smart Citation
“…Only 11% of respondents in this study wear facemask at all the times when they are outdoor and in the public. In other related studies nearly half of the respondents used facemask regularly when outdoor [19,26,27]. Furthermore 18% and 24% of the respondents in this study respectively wear and remove their facemask appropriately in accordance with the protocols on wearing and removal of facemask.…”
Section: Recommendationmentioning
confidence: 51%
“…While the 2019 Global Health Security Index found that no country was fully prepared for a pandemic, the African region had the lowest scores. 20 Recent studies from South Africa 21 , Nigeria 22 , Ethiopia 23 and Libya 24 illustrate the need for improved coverage of basic IPC training amongst frontline HCW of all cadres, an initiative which should ideally be built into both pre-service education and in-service training in all countries. Training alone is insufficient to close the IPC performance gap -enabling policies, guidelines, systems, supplies, and infrastructure are also essential.…”
Section: Introductionmentioning
confidence: 99%